E-Santri Sebagai Aplikasi Pembelanjaan dan Pembayaran Mandiri oleh Santri di Pondok Pesantren Az Zubair - Moh Zayyadi; Abd Wahab Syahroni (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2020)
Shopping, sanctions and payment transactions at the Az Zubair Islamic Boarding School still use the manual transaction system, using manual notes and cash. Some of the transactions in Islamic boarding schools include monthly payment transactions, mini markets or canteen, payment for services and payment of fines or penalties. Transactions that are carried out manually are very prone to theft and difficult to trace, difficult to recapitulate and can be one of the transmissions of germs, bacteria or viruses that stick to cash. The application of the eSantri as an independent spending and payment application by students at the Az Zubair Islamic Boarding School aims to provide information openly and directly to students regarding the payment of students obligations, train students to be familiar with non-cash transactions even though it is only done in the local boarding school network using a card students in which there is a password and balance. The implementation method used is socialization and training. The application development method uses the prototype method. After the application is made, the team conducts training for students, besides that the team has also made a manual book for using the eSantri application. This activity was carried out from April to August 2020. Based on the results of a survey of 80 responden using a Likert scale on the implementation ot the eSantri application in Islamic boarding schools, they strongly agreed with this activity with a satisfaction percentage value of 81.75%.